Eksplorasi Data Sains dalam Pendidikan: Membuka Wawasan Baru untuk Siswa SMA - Athoillah, Muhammad; Rochmanto, Hani Brilianti; Wae, Maria Yohana Vianey; Rokhmania, Nina Anggraini Junet (PT. Riset Press International, 2025)
Data science literacy is an important skill in the digital era, but high school students' understanding of this concept is still limited. This study aims to improve students' data science literacy through interactively designed training, including theory delivery and discussion sessions. This study was conducted in Surabaya involving 32 students from five partner schools. The research instruments included a pre-training questionnaire to measure the level of initial understanding, training materials in the form of presentations and educational case studies, and a post-training questionnaire to evaluate the results. The analysis was carried out quantitatively based on the results of the pre-test and post-test, and qualitatively through observation and discussion. The results showed a significant increase in student understanding, with the average post-test score increasing from 45% to 80%. Positive responses from students and teachers indicated that the case study-based training approach was relevant and effective. However, obstacles such as differences in student understanding levels and limited training duration were obstacles to implementation in maximizing knowledge for participants.